877 The occupational safety & health (osh) in india: the current scenario. (24th April 2018) - Roy, Priyanka
Abstract : Introduction: Occupational Safety and Health (OSH) is an important for the health and well being of the workers to ensure the hazard free workplace, reduces absenteeism and enhancing the productivity by properly addressing the safety and health issues of the employees. Though India has reached to high rate of growth due to industrialization over the period, the challenge continues to ensure the OSH culture at workplace. Methods: This is an analysis of all Government documents related to Labour Act of India. Total 51 documents were retrieved from the Ministry of Labour and Employment (India) website with a search strategy. All documents were classified into 7 themes: industrial relations; wages; working hours; conditions of service and employment; equality and empowerment of women; disadvantageous sections of the society; social security. Each category was analysed using the search engine 'occupational safety and health' or 'occupational health and safety'. The Labour Rules under Labour Act were excluded as those are varied state to state. Since the study used data available in public domain and no human participants were involved it did not require ethics committee approval. Results: After extraction and analysis of all documents it was identified that the comprehensive safety and health statutes for regulating OSH at work places exist only in respect of the four sectors: the Factories Act, 1948; the Mines Act, 1952; Dock Workers Act, 1986; the Building and Other Construction Workers Act, 1996. There is no separate entity of legislation under the framework of OSH. Discussion: Although it is enshrined in the Constitution and the Legislature of India, the traditional concepts of OSH prevailing in the country is a far cry from the objectives of the ILO and international standards for OSH. Being a signatory participant for Convention 187 India has to comply with OSH in near future.